The effect of coarse to fine aggregate ratio on the fresh and hardened properties of roller-compacted concrete pavement - Hashemi, Mohammad; Shafigh, Payam; Karim, Mohamed Rehan; Atis, Cengiz Duran (Elsevier, 2018)
Roller-compacted concrete pavement (RCCP) is an economic and durable rigid pavement. Although about half century has passed since the first RCCP was implemented, information about this type of concrete is still limited. RCCP as a zero-slump concrete, has lower cement content than conventional vibrated concrete. Therefore, the quality of the aggregates has a significant impact on the properties of concrete. For this reason, the quantity of coarse and fine aggregates in RCCP should be optimized. This study investigates the effect of coarse to fine aggregate (C/F) ratio on the fresh and hardened properties of two RCCPs with cement contents of 9% (204 kg/m 3 ) and 12% (268 kg/m 3 ). Compressive strength, splitting tensile strength, flexural tensile strength, Vebe time and porosity tests were carried out. The test results demonstrate that increasing the C/F ratio from 0.6 to 1.8 increased the Vebe time threefold, while increasing the cement content from 9% to 12% decreased the Vebe time by 12%. In addition, increasing the C/F ratio from 0.6 to 1.2 significantly decreased the porosity of RCCP, to about 60% for RCCP with 9% cement and 38% for RCCP with 12% cement. Generally, the most suitable C/F ratio for RCCP appeared to be from 1.2 to 1.4. Thus, to attain a workable, high-strength and durable RCCP, a mix with 12% cement and 1.2C/F ratio is recommended.